Learning trajectory menggunakan model pembelajaran discovery learning pada materi barisan aritmetika - Rengganis, Renti; Hidayat, Wahyu (IKIP Siliwangi, 2025)
This research aims to produce learning trajectory by using discovery learning model on arithmetic sequence material. Researchers used the design research method which has three stages, namely preliminary design, design experiment, and retrospective analysis. This research was conducted at SMA Al Bidayah Batujajar on class X-1 students consisting of 20 students. Based on the results of the research, a learning trajectory was obtained that could help students understand the concept of arithmetic sequence consisting of activities to understand number patterns, identify differences and nth terms, discover the concept of arithmetic sequence, and apply the concept of arithmetic sequence in real life. The results of the learning experiment using the discovery learning model can help students improve their understanding of the concept of arithmetic sequence.